PENYULUHAN TENTANG MANFAAT MENGKONSUMSI TELUR REBUS AYAM RAS TERHADAP PENINGKATAN HAEMOGLOBIN IBU HAMIL - Tetty Junita Purba; Husna Sari; Marlen Sadrina Sitepu; Erlina Hayati; Stefani Anastasya Sitepu; Nurmala Sari (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Pregnancy is a condition that occurs naturally in obtaining offspring, which physiologically occurs in the mother's womb. The pregnancy process will definitely have a big impact on the pregnant woman's body. The hematological system is one of these changes. The impact of these changes often results in anemia during pregnancy. In developing countries, around 30% of the population experiences anemia. Apart from medicines that can prevent anemia, consuming boiled eggs is also an effort to reduce the incidence of anemia in pregnant women. This is because the ingredients contained in purebred chicken eggs include various vitamins and minerals, including vitamin A, riboflavin, folic acid, vitamins B6, B12, choline, iron, calcium and phosphorus. This outreach activity was carried out with the aim of providing information about the benefits of purebred chicken eggs in terms of increasing hemoglobin in pregnant women.